Karol Lilienfeld-Krzewski i jego rola w budowaniu legendy legionowej Józefa Piłsudskiego - Czekaj, Katarzyna (Acta Universitatis Lodziensis. Folia Historica, 2008)
This article is an attempt of showing the role in building an ethos of legion and the legend of Józef Piłsudski by literary work of Karol Lilienfcld-Krzcwski. This figure although of its unquestionable input in the activity has gone into forgetfulness, that’s why his life, as well as the rich literature, jurnalist and his publicity work is worth mentioning. Karol Krzewski wasn’t the first plan activist, although his participation in many important events, entrusting to positions less prominent but often crucial to the authorities, lastly the remarkable personality, made him highly valued figure in political circles and popular among wide masses of community of the 11 RP (Pepublic of Poland). The participant of a Riflemen’s Association in Galicja, a soldier in The First Brigade of Polish Legions, an activist in Polish War Organization, the participant of war 1920, (political) commentator of the belweder camp, one of the founder of its political programme, the member of Polish Radio’s management, employee of the Military Institute of Science and Education, lastly a soldier of the September campain and an associate of Marszalek Śmigly-Rydz while his residence in Romania - Krzewski’s life and carier was determined by the most important attempts in the history of two decades of the XX-th century. Although in the awarncss of the contemporaries Krzewski remained popular Kapra! Szczapa, which adventure became the basis of a book, that made its author not only famous but also built one of the legends around the figure of Józef Piłsudski. The authoress of this article tried to show (point out) the most characteristic elements of this legend, as well as the whole legion mythology, presented in Krzewski’s work. She analized not only the literary work Kapral Szczxtpa but also the work conected with the legion and military campsite theatre press. The analizę, in confrontation with other similar front-line publications, alowed to place Szczapa in the rich trend of legion literacy. Krzewski’s work in this period: literary, in the front-line publications and on the stage of campsite theatre was the reflection of consolidation process which occured in the group associated with Józef Piłsudski, the document of the reality in military service and life in the dig in around Wołyń, lastly the reflection of political conflicts of those times. Worth mentioning is the original, unique language, which uses Krzewski and wich is the characteristic for the whole legion environment, codc understood and used only by the soldiers of this concrete military unit. Another specific element is the always present and unique military humor, very well seen in Kapral Szczapa. What strikes is its sharp, mockery and malice. The language and humor are mostly used to propagate the glory of First Brigade and her Commanding oficer. The next thing that strikes is the uncritical relation to the decisions, plans, resolutions o f Piłsudski and the recognition of elitisty o f his soldiers. Krzewski’s work is also a proof of how strong and deeply ingrained in those times was the cult of Józef Piłsudski among the members of his camp. The conflicts inside the whole political camp found also a reflection in Kapral Szczapa. There are lots of mockery and malice remarks about the Military Department NKN, the members of Legion Headquarters, contemptuous attitude to the Austrian headquarters and the whole c.k. army. To sum up, this article is ment to show the impact and popularity, which Kapral Szczapa recieved (obtained) not only at war among followers of Józef Piłsudski. At the same time this work is a document of its age, original historical source, the work of creative inteligence, which concentrated around Józef Piłsudski in the times of First World War and which gave the beginning to the strongest political camp in the II Republic of Poland.